The Mediating Effect of Resilient Leadership on MSMEs' Capabilities in Indonesia - Widakdo, Danang Sudarso Widya Prakoso Joyo; Bachtiar, Riza Rachimi; Rusti, Nanda; Halil, Halil; Wicaksono, Driyanto Wahyu; Nur, Kurniawan M. (Jurnal Penyuluhan, 2026)
Micro, small, and medium enterprises (MSMEs) account for 60% of Indonesia's gross domestic product and employ 97% of the formal workforce. Despite their economic significance, MSMEs encounter persistent challenges, including economic instability, digital transformation, and human resource development. This study examines the impact of intellectual, emotional, and spiritual intelligence on the capabilities of MSMEs, with resilient leadership serving as a mediating variable. The research involved 223 food and beverage MSMEs located in Jember, Bondowoso, Lumajang, and Banyuwangi regencies. Data were collected through proportional random sampling using a 5-point Likert Scale and analyzed using path analysis. This research is grounded in several related theoretical frameworks from the empirical literature, including transformational leadership theory, collaborative leadership theory, and extension theory as the grand theory The results indicate that all three forms of intelligence significantly affect both resilient leadership and MSME capabilities, with resilient leadership mediating these relationships. Intellectual intelligence supports strategic analysis (mean score: 4.21), emotional intelligence fosters effective interpersonal relationships (mean score: 4.8), and spiritual intelligence informs ethical decision-making (mean score: 4.15). As this study is limited to the food and beverage sector, future research should examine additional sectors and variables. The findings provide evidence-based recommendations for enhancing the resilience of MSMEs in response to global challenges.